Raising and educating a deaf child - Marschark, Marc. 4 0 16; 5 (New York : Oxford University Press, 1997)
In Raising and Educating a Deaf Child, Marc Marschark offers parents and teachers a readable and comprehensive summary including everything a parent would want to know about growing up deaf. Parents of a deaf child, like the parents of any child, want to know the answers to some apparently straightforward questions, such as What kind of school will provide my child with the best education? What language experience is best for my child, sign or speech? Will my child be able to get a good job? Marschark addresses these questions and more, with topics ranging from what it means to be deaf and the uniqueness of Deaf culture to the medical causes of early hearing loss, from technological aids for the deaf such as TTYs and cochlear implants to the educational and social opportunities available to deaf children. He describes the many ways that the environment of home and school can influence a deaf child's chances for success in both academic and social circles. Above all, he emphasizes the need for early detection of hearing loss and the importance of being able to communicate with deaf children from a very early age, recommending that parents of deaf children learn sign language and use it often. This is not a how to book or one with all the right answers for raising a deaf child. This is a guide through the many conflicting suggestions and programs for raising deaf children, as well as the likely implications of taking one direction or the other.
Foreword /;A Deaf Child in the Family --;Practical Aspects of Being Deaf --;Communicating with Deaf Children --;Early Interactions: The Roots of Childhood --;Language Development --;Going to School --;Learning to Read and Write --;Intelligence, Achievement, and Creativity --;Deaf Children to Deaf Adults --;Where Do We Go from Here? --;Information Sources and Organizations Serving Deaf Children. 1.;2.;3.;4.;5.;6.;7.;8.;9.;10. Sandy Harvey --
Includes bibliographical references (p. 215-220) and index.
Keywords: 2 -- 0; 6; Language. -- Deaf children.;Deaf children;Parents of deaf children.;Deafness;Persons With Hearing Impairments;Parenting;Education, Special;Infant.;Child. -- 20 -- Popular Works.;Popular Works.;Popular Works.;Popular Works; 20; 2